Pengaruh Bahan Ajar Berbasis Audiobook Terhadap Hasil Belajar Siswa di Sekolah Dasar - Ari Metalin Ika Puspita; Flora Puspitaningsih; Yoyok Nur Cahyono (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2022)
The problems found in the field based on observations in the field are that the existing teaching materials do not attract students' interest and student learning outcomes are still low. The problem is the unavailability of teaching materials that are innovative and attract students to be motivated to learn. This causes students to have difficulty absorbing and understanding the material taught by the teacher. The purpose of this study was to see the effect of implementing audiobook-based teaching materials on student learning outcomes. The research method used in this research is a quantitative research type with a quasi-experimental type. In this research design, the researcher used an experimental group with a control group, which was started by giving a pretest to each group. The population in this study were students at SDN 4 Pule, Trenggalek Regency. The sampling technique used is purposive sampling, namely the sample used is fourth grade students at SDN 4 Pule, Trenggalek Regency. The instruments used in this study were observation sheets, interview guidelines, and tests. While the data analysis technique used is independent sample t-test with the help of SPSS 25.0 software. The results of this study indicate that the use of audiobook-based teaching materials has an effect on differences in student learning outcomes before and after the use of audiobook-based teaching materials, so audiobook-based teaching materials can improve learning outcomes and students become motivated in learning because students can understand the material without reading.